Study of the Growth Process of Original Crack in the Surrounding Rock of Tunnel under the Adjacent Explosive Load - Kang Liu; Dongming Guo; Xinchao Kang; Jun Zhang (Shock and Vibration)
The surrounding rock damage of a tunnel under adjacent explosive load is often manifested as the growth of the original crack. In order to thoroughly understand the crack growth mechanism, in this study, the growth process of the original crack was investigated in detail by the dynamic caustics experiment. The experimental study shows that the growth of original crack is the result of the combined action of explosion stress wave and explosive gas. The quasi-static stress generated by the explosive gas was superimposed on the weakened stress field, resulting in the formation of the peak of the main stress difference in the surrounding rock, moving towards the adjacent tunnel in the form of an arc wave. With the arc wave moving towards the original crack, the growth rate of the original crack increases rapidly. During the period of 200 μs to 250 μs, the crack growth rate oscillates at the peak, and its size is approximately equal to the moving speed of the arc wave. Based on the experimental results and microscopic damage mechanics, the high stress concentration at the original crack tip under the stress wave first causes damage localization and the weakest chain is formed by the penetration of the damage localization zones by microcracks by special distribution law. Subsequently, the original crack starts to initiate and grow along the direction of the weakest chain.